The spatiality of the soybean crop water deficit in Jales and Andradina microregions, state of Sao Paulo - Credo Assis, Kamila Cristina de; Lelles Moreira Begueline, Maria Clara [UNESP]; Costa, Joao Victor [UNESP]; Tangerino Hernandez, Fernando Braz [UNESP] (Inst Federal Sul Minas Gerais-i Fsuldeminas, 2021)
Knowledge about soil water availability for future planning is the basis for carrying out its rational use. This work aimed to study the spatiality of water precipitation, crop evapotranspiration, and the need for water supplementation in soybean cultivation in the microregions of Jales-SP and Andradina-SP for the summer harvest. The water balance was determined by the Thorthwaite and Mather (1955) method, with data made available by the Agrometeorological Stations Network operated by the Hydraulics and Irrigation area of UNESP Ilha Solteira. We considered an available water capacity (AWC) of 40 mm. The study took place from the simulation of the water condition of a soybean crop sown on November 4, 2020. In the water deficit condition, the actual evapotranspiration (ETa) was considered null at a 20 % deficit, and the other values followed the same mathematical proportion. The mean rainfall of the period, crop evapotranspiration, and water deficit of each weather station were interpolated through ordinary circular kriging in ArcGIS 10.7 software. The water deficit in the soybean crop in the northwest region of Sao Paulo is related to the poor distribution of precipitation during the cycle and the significant recurrence of Indian summers all through the area. For the producers' safety, investment in irrigation systems anticipating this poor distribution is justified. The water deficit in the region is variable. In years with good rainfall distribution, it can reach zero values, and in years with poor distribution, it can reach values greater than 180 mm.
Keywords: Water Balance; Irrigation; Kriging; Northwest of the state of Sao Paulo